An Analysis of Students’ Strategies in Writing Recount Text - Shindy Ika Lestari Chandra; Syarifuddin Dollah; Geminastiti Sakkir (PT ARRUS Intelektual Indonesia, 2024)
This study aimed to find out strategies for students in writing recount text. This research design used a descriptive qualitative method. The subject of the research was students in Grade 8th in SMP Laniang Makassar in the academic year 2022/2023. The sample was 22 students in two classes and used purposive sampling to gain the data. The data was collected using interviews. Based on the researcher’s result, the researcher found that there were various strategies to overcome problems encountered by the students in writing recount text, namely the strategy of (1) making lessons visually compelling, (2) identifying important ideas, (3) changing vocabulary by students, (4) changing evaluations, and the last (5) linking previous knowledge. The positive response from students to this strategy indicates how crucial it is to encourage the development of comprehensive and in-depth writing skills. As a result, implementing an adaptive and responsive learning strategy can help students become better writers and produce graduates who are prepared to meet the demands of both academic and professional English.